Mission San Carlos Borromeo de Carmelo [facade and south side of building] - Lewis Josselyn:::::: (1926)
The mission standing at the end of the path approaching from the west, with fencing lining the pathway. A large hill rises to the left of the mission, and a sliver of the ocean is in the background.